Value and Cost Savings From Access to Multi-disciplinary Rehabilitation Services After Severe Acquired Brain Injury - Lorenz, Laura S.; Doonan, Michael (Frontiers in Public Health, 2021)
Acquired brain injury (ABI) is a major global public health problem and source of disability. A major contributor to disability after severe ABI is limited access to multidisciplinary rehabilitation, despite evidence of sustained functional gains, improved quality of life, increased return-to-work, and reduced need for long-term care. A societal model of value in rehabilitation matches patient and family expectations of outcomes and system expectations of value for money. A policy analysis of seven studies (2009–2019) exploring outcomes and cost-savings from access to multi-disciplinary rehabilitation identified average lifetime savings of 1.50M per person, with costs recouped within 18 months. Recommendations: Increase access to multi-disciplinary rehabilitation following severe ABI; strengthen prevention focus; increase access to case management; support return-to-work; and systematically collect outcome and cost data.